Management of climatic heat stress risk in construction: a review of practices, methodologies, and future research - Rowlinson, S.; Jia, Andrea; Li, B.; Chuanjing, C. (Elsevier Ltd, 2014)
Climatic heat stress leads to accidents on construction sites brought about by a range of human factors emanating from heat induced illness, and fatigue leading to impaired capability, physical and mental. It is an occupational characteristic of construction work in many climates and the authors take the approach of re-engineering the whole safety management system rather than focusing on incremental improvement, which is current management practice in the construction industry. From a scientific viewpoint, climatic heat stress is determined by six key factors: (1) air temperature, (2) humidity, (3) radiant heat, and (4) wind speed indicating the environment, (5) metabolic heat generated by physical activities, and (6) “clothing effect” that moderates the heat exchange between the body and the environment. By making use of existing heat stress indices and heat stress management processes, heat stress risk on construction sites can be managed in three ways: (1) control of environmental heat stress exposure through use of an action-triggering threshold system, (2) control of continuous work time (CWT, referred by maximum allowable exposure duration) with mandatory work-rest regimens, and (3) enabling self-paced working through empowerment of employees. Existing heat stress practices and methodologies are critically reviewed and the authors propose a three-level methodology for an action-triggering, localized, simplified threshold system to facilitate effective decisions by frontline supervisors. The authors point out the need for “regional based” heat stress management practices that reflect unique climatic conditions, working practices and acclimatization propensity by local workers indifferent geographic regions. The authors set out the case for regional, rather than international, standards that account for this uniqueness and which are derived from site-based rather than laboratory-based research.